2020
DOI: 10.1002/pat.5133
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of meltable and highly thermostable triazine‐DOPO flame retardant and its application in PA66

Abstract: A melting phosphorous‐nitrogen flame retardant was synthesized via the addition reaction of 9,10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO) and 2,4,6‐triallyloxy‐1,3,5‐triazine (TAC). The synthesized product from DOPO and TAC (DT) flame retardant possesses high thermal stability with T5wt% at 340°C, which can meet the high‐temperature processing for polyamide 6,6 (PA66) and other engineering plastics. The chemical structures of DT were characterized by nuclear magnetic resonance and infrared spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…A sharp endothermic peak is observed at around 123.3 °C in the DSC curve, which is assigned to the melting of DOPO. 25 It is also found that the initial degradation temperature of DOPO is determined to be 211.1 °C.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…A sharp endothermic peak is observed at around 123.3 °C in the DSC curve, which is assigned to the melting of DOPO. 25 It is also found that the initial degradation temperature of DOPO is determined to be 211.1 °C.…”
Section: Resultsmentioning
confidence: 94%
“…9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) (the chemical structure is shown in Figure a), as a typical phosphaphenanthrene-based flame retardant, has the advantages of less smoke (Figure S1), low toxicity, low cost, and highly efficient fire retardancy, which is one of the most widely used retarding agents in the polymer industry. Initially, Li et al encapsulated DOPO in the cathode material to improve the fire extinguishing performance of the cathode. However, they fail to address the flammability of the electrolyte and the capsule preparation process is usually too complex to industrialize.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] There has been reported that the flame-retardant efficiency of DOPO can be further improved through the molecular design method. [16][17][18] Thereinto, introducing the nitrogen-containing group (such as triazine, [19,20] triazinetrione, [21][22][23] Schiff-base, [24][25][26] and hexachlorocyclotriphosphazene [27,28] ) is a feasible way. The phosphophenanthrene group and nitrogen-containing group can exert a P−N synergistic flame-retardant effect to improve the flame retardancy of epoxy thermosets.…”
Section: Introductionmentioning
confidence: 99%
“…It is particularly important to improve the flame retardancy of PA66 [ 1 ]. Currently, flame retardants are usually added to improve the flame retardancy of PA66, such as halogenated flame retardants decabromodiphenyl ether [ 2 ], metal hydroxide [ 3 ], nano clay [ 4 ], nitrogen compounds [ 5 ], and phosphorus-containing organic compounds [ 6 ]. Because halogenated flame retardants are prone to produce toxic and corrosive smoke and gas during combustion, they easily corrode equipment, harm the environment, and harm the human body.…”
Section: Introductionmentioning
confidence: 99%